The accuracy of cross-country valuation by multiples using comparables – the cultural aspect - Schøler, Finn (Archives of Business Research, 2020)
We study the accuracy of using traditional multiples valuation method in a global setting. The method of comparables refers to the valuation of companies based on multiples of comparable (similar) companies, preferably from same industry. While this may lead to accurate valuations of comparables from one country, it is often not the case for global comparables due to cross-country differences in culture, economics and accounting practice. We selected all listed non-financial companies with non-negative earnings and equity from the global ORBIS-database, i.e. 16,898 companies from 112 countries. PWC’s publication on contemporaneous adoption and use of IFRS, helped us categorise each country’s accounting regime as requiring, permitting or disallowing IFRS for listed companies. Hofstede’s cultural indexes adapted to Gray’s accounting values where used to categorise cultural differences. Finally, we chose the P/E, P/B, P/S, EV/S and EV/EBITDA ratios as our multiples. We find that the traditional focus on industry alone is not the best way to estimate a company’s value based on multiples. Different attitudes towards selection of comparables lead to differences in valuation precision due to differences in accounting tradition and culture in various countries. Consequently, the cultural aspect should be taken into consideration when choosing comparables across countries.